Downregulated miR-195 Detected in Preeclamptic Placenta Affects Trophoblast Cell Invasion via Modulating ActRIIA Expression - Bai, Yang; Yang, Weiwei; Yang, Hui-xia; Liao, Qinping; Ye, Gang; Fu, Guodong; Ji, Lei; Xu, Peng; Wang, Hao; Li, Yu-xia; Peng, Chun; Wang, Yan-ling (PloS one, 2012)
Preeclampsia (PE) is a pregnancy-specific syndrome manifested by on-set of hypertension and proteinuria after 20 weeks of gestation. Abnormal placenta development has been generally accepted as initial cause of the disorder. Recently, miR-195 was found to be down-regulated in preeclamptic placentas compared with normal pregnant ones, indicating possible association of this small molecule with placental pathology of preeclampsia. By far the function of miR-195 in the development of placenta remains unknown. Bioinformatic assay predicted ActRIIA as one of the targets for miR-195. By using Real-time PCR, Western blotting and Dual Luciferase Assay, we validated that ActRIIA was the direct target of miR-195 in human trophoblast cells. Transwell insert invasion assay showed that miR-195 could promote cell invasion in trophoblast cell line, HTR8/SVneo cells, and the effect could be abrogated by overexpressed ActRIIA. In preeclamptic placenta tissues, pri-miR-195 and mature miR-195 expressions were down-regulated, whereas ActRIIA level appeared to be increased when compared with that in gestational-week-matched normal placentas. This is the first report on the function of miR-195 in human placental trophoblast cells which reveals an invasion-promoting effect of the small RNA via repressing ActRIIA. Aberrant expression of miR-195 may contribute to the occurrence of preeclampsia through interfering with Activin/Nodal signaling mediated by ActRIIA in human placenta.